Influence of degree of cold-drawing on the mechanical properties of low carbon steel (2011)
Low carbon steel metal is used for the manufacture of nails. Steel wire with <0.3% C content is cold-drawn through a series of drawing dies to reduce the diameter of the wire to the required diameter of the nails. A 0.12%w C steel wire cold drawn progressively by 20%, 25%, 40% and 50% was investigated. The influence of the degree of cold drawing on the mechanical properties of the carbon steel material were studied using the tensile test, impact test and hardness test experiments in order to replicate the service condition of the nails. The tensile test was done on a Montanso® tensometer to investigate the yield strength and the tensile strength of the material as the degree of deformation increases. An Izod test was used to determine the impact toughness of the steel using the Hounsfield impact machine and the hardness numbers were obtained for the different degrees of drawn deformation of the steel on the Brinnel tester. The study used the stress-strain relationship of the tensile test experiment to study the effect of the degree of cold-drawing deformation on the yield strength and tensile strength properties of the low carbon steel. The yield strength of the material was observed to reduce with increasing degree of cold-drawing, an indication of reduction in the ductility and the tensile strength of the material reduced with increasing degree of cold-drawn deformation. The ability of the material to resist impact loads when nails are hammered reduced with increasing degree of drawn deformation as a result of strain hardening of the material after the drawing operation. However the resilience of the material to further cold drawn deformation increased with increasing degree of deformation as evident in the Brinnel hardness number which in-creases with the degree of drawing deformation. This is an indication of the material’s approach to brittleness as the degree of drawn deformation increases